O diagnóstico de transtorno de conduta: incidências no campo da saúde mental da infância e adolescência - Perez, Camila Deneno (2017)
This dissertation has as main objective the problematization of the diagnosis of conduct disorder directed to children and adolescents. More specifically, this study proposes to 1) to contextualize historically the emergence of this classification in psychiatry, as well as the questions raised in this segment; 2) to characterize and analyze some of its implications in the field of childhood and adolescence mental health. The methodological strategies were based on clues of the genealogy proposed by Michel Foucault and on the contributions of the French Institutional Analysis. From the point of view of the procedures adopted, we tracked the notion of "conduct disorder" in the Diagnostic and Statistical Manual of Mental Disorders (DSM) and its modulations in different editions, as well as highlighting positions that question such a psychopathological classification in psychiatric child-juvenile manuals. We also discuss the forensic uses and the psi-juridical articulation (re)produced by this diagnosis. A second dimension of the research, of an empirical nature, sought to analyze some of its uses and effects in a mental health service destined to children and adolescents through the monitoring, in the case-tracer strategy, of a case considered conduct disorder in a child-juvenile CAPS. As an analytical perspective, we use contributions from Michel Foucault on the psychiatry of childhood and the institution of abnormality as a mechanism for governing lives. We conclude that the classification of "conduct disorder" supports control and normalization actions, since it validates the correction of rebelliousness and inequality, decontextualized and circumscribed as deviant conduct. We consider that these reflections, related to child-juvenile mental health, can favor the construction of affirmative practices of the difference, the singularity and the unpredictability of childhood